1990
DOI: 10.1177/001872089003200301
|View full text |Cite
|
Sign up to set email alerts
|

Maps or Analogies? A Comparison of Instructional Aids for Menu Navigation

Abstract: We investigated the relative efficacy of a variety of spatial maps and analogies as instructional aids for the learning and navigation of hierarchical data bases. Subjects performed single- and multi-node retrieval tasks with novel data bases. The results of Experiment 1 indicated that subjects who studied an analogy prior to performing data retrieval tasks were less affected by increasing search distance than were subjects who studied a spatial map. The results of Experiment 2 suggested that the benefits of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…These include studies of orientation and navigation (e.g. Wright & Lickorish, 1989;Webb & Kramer, 1990), comparisons of hypertext and other formats (e.g. Gray & Shasha, 1989;Beard & Walker, 1990;Leventhal, Teasley, Instore, Rohlman & Farhat, 1993) and investigations into the relationship between task type and information structure (Rada & Murphy, 1992;Mohageg, 1992).…”
Section: Measuring Hypertext Usabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…These include studies of orientation and navigation (e.g. Wright & Lickorish, 1989;Webb & Kramer, 1990), comparisons of hypertext and other formats (e.g. Gray & Shasha, 1989;Beard & Walker, 1990;Leventhal, Teasley, Instore, Rohlman & Farhat, 1993) and investigations into the relationship between task type and information structure (Rada & Murphy, 1992;Mohageg, 1992).…”
Section: Measuring Hypertext Usabilitymentioning
confidence: 99%
“…However, it is suggested here that the concept of ''errors'' is inappropriate for a hypertext system which is specifically designed to facilitate browsing and exploration. Deviations from an ''optimal'' path required to complete a task have also been considered as a measure (Simpson & McKnight, 1989;Webb & Kramer, 1990;Mohageg, 1992) but this still discourages exploration. Nevertheless, it can be useful to consider what users are doing when they deviate from such a path.…”
Section: Measuring Hypertext Usabilitymentioning
confidence: 99%
“…In parallel initiatives, browsing research has taken a strong developmental focus. Problems are resolved with tools such as overview maps of hypertext links and nodes (Hammond & Allinson, 1987), electronic bookmarks (Billingsley, 1982;Webb & Kramer, 1990), history lists (Foss, 1989), guided tours (Hammond & Allinson, 1987), "sh-eye views (Gecsiu & Martin, 1989), thumbnail sketches (Nielsen, 1990) and three-dimensional graphical techniques (Mackinlay, Robertson & Card, 1991;Williamson & Shneiderman, 1992;Rada, Wang & Birchall, 1993;Card, Robertson & York, 1996). All purport to aid the information seeker.…”
Section: Facilitating Browsingmentioning
confidence: 99%
“…There have been a number of studies on the aiding tool to support menu search (Billingsley, 1982;Han & Kwahk, 2000; E. S. Lee & MacGregor, 1985;Mayson-Maddison & Lee, 1982;Roske-Hofstrand & Paap, 1986;Snowberry, Parkinson, & Sisson, 1983Webb & Kramer, 1987, 1990. Roske-Hofstrand and Paap showed that the users can benefit from highly redundant links among nodes.…”
Section: Introductionmentioning
confidence: 99%